Effect of High Performance Work System (HPWS) on Service Employees Performance in the Automotive Retail Industry - Rani, Rashida Mat; Normy Rafida Abdul Rahman; Nurul Aqilah Mohd Yusak (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study investigates the effects of perceived high performance work system (HPWS) on employee performance in the Malaysian automotive service industry. It also attempts to examine the mediating roles of perceived organisational support and psychological empowerment in the relationship between HPWS and employee performance. Design/Methodology/Approach: Data were collected from 391 employees working in automotive after sales service centres in Kuala Lumpur and Selangor. Multiple regression analysis was performed to examine the proposed relationships. Research findings: The findings demonstrated substantial evidence of the relationship between perceived HPWS and employee performance. This relationship was mediated by perceived organisational support and psychological empowerment. Theoretical contribution/Originality: This study extends on the existing literature by investigating how perceived HPWS can lead to employee performance within the context of the service sector. Practitioner/Policy implications: The outcome of this research suggests that human resource practitioners in the automotive service industry should pay attention to the implementation of HPWS to survive in today’s business environment. In developing HPWS, employees’ perceptions of HRM practices should be carefully evaluated in order to achieve a win-win situation. The perception of employees on HPWS can improve their performance if organisations provide the necessary support and empowerment. Research limitation: Since the data were collected from the automotive service industry in Malaysia, the results may need to be interpreted cautiously, due to the issue of generalisability. Keywords: High-Performance Work System (HPWS), Human Resource Practices, Perceived Organisation Support (POS), Psychological Empowerment (PE), Service Employee Performance (SEP) JEL Classification: M12